The Method of Coloring Techniques to Enhance Creativity in The Product Creation of Pandanus Wickerworkers in Sungai Bakau, Ketapang : Teknik Pewarnaan untuk Peningkatan Kreativitas dalam Penciptaan Produk Perajin Anyaman Pandan Sungai Bakau, Ketapang - Sulistyaningtyas, Tri; Suryani, Yani; Dewanti, Sira Kamila; Hendriyana, Husen; Widiawati, Dian (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service activities was conducted in Ketapang, West Kalimantan. Ketapang is a coastal area with abundant natural resources, one of which is the pandanus plant. Pandanus plants are utilized by the Ketapang community to become the basic material for handicrafts by craftsmen. The pandanus crafts produced by the craftsmen contain Ketapang's cultural identity. However, the craftsmen do not have knowledge of natural coloring techniques so that the products produced are monotonous. This activity aims to increase the independence and creativity of pandan embroidery crafters through coaching and mentoring. This service uses a participatory method so that all crafters are actively involved during the activity. The result of this activity is an increase in the creativity of pandan embroidery crafters in Ketapang. Providing material on natural coloring techniques can increase the creativity of crafters. This activity opens opportunities for Ketapang crafters to introduce their cultural identity while increasing the income of Ketapang crafters' Organitation. This activity also provides an understanding of sustainable products that support environmental preservation.